Nonlinear seismic analysis of a train-tunnel-soil system and running safety assessment of metro vehicles. Issue 147 (August 2021) - Li, Junjie; Lou, Yunfeng; Yang, Xun; Jin, Xianlong
Abstract: Since earthquakes would pose a serious threat to the safety of underground railway tunnels and subway trains, the seismic analysis of the subway tunnel and the metro train is essential for earthquake-resistant design and construction. This presented study aims to investigate the transient response of a train-tunnel-soil coupled system under various load conditions, and assess running safety of the moving train. Firstly, a simulation model of the train-tunnel-soil system was established, considering interactions between soil and tunnel, rail and train. Secondly, the numerical approaches employed in this paper were verified, and the tunnel-soil model was validated with the available test data. Finally, the nonlinear seismic response of the train-tunnel-soil system is investigated, and running safety indices of the subway vehicle are evaluated. Moreover, the effect of train speed and earthquake intensity on the running safety of the metro train is assessed. The numerical results reveal that compared to the moving-train load, the effect of earthquake action on the dynamic response of the subway tunnel is more prominent, resulting in a significant increase of the wheel-rail force and acceleration of the railway vehicle. Both earthquake loads and train speed have an impact on running safety indices, while the earthquake intensity has a more significant effect on the safety index of the metro vehicle. Moreover, it is worth noticing that with respect to the designed operational speed of 90 km/h for Nanjing Metro Line 10, the ability of the metro train to withstand earthquake excitation is no more than a maximum acceleration of 0.2 g. Highlights: Predicting the normal force, separation and derailment factor between wheel and rail. Application of a train-tunnel-soil coupled system due to seismic excitation. Assessing the running safety of a metro train passing through a tunnel under earthquakes. Evaluating the effect of the earthquake intensity and the train speed on the running safety of the subway vehicle.